Management in the Public Broadcasting Service: The Reasons for a Change of Strategy - Ratković Njegovan, Biljana; Radenković, Vladimir (International Journal of Industrial Engineering and Management, 2010)
Being faced with massive competition, public service broadcasters are in a constant struggle for audiences’ attention, and are increasingly changing their outdated, patriarchal and elitist position in order to radically modernize. For public broadcasters the choice of future business strategy depends on their capability to introduce technological changes and provide linear broadcasting and non-linear media, as well as on the quality of programming that can resist the pressure of private broadcasters’ competition. That is why the time is ripe for a transitional transformation of the PSB in order to bridge the gap between senders and receivers of media messages. Over the course of this transition the public service broadcasting develops into the public service media. The intensive orientation of media firms to portfolio strategies is due to diversity of their production programme, increased and diversified business areas of their interest, as well as to the necessity of simultaneous development of new business concepts and communication products. Media companies have to be flexible enough to respond to the challenges of the digital switchover and fragmentised audience, while still promoting public interest as the guiding principle of their business management. Article history: Received (21.09.2010); Revised (13.10.2010); Accepted (25.10.2010)